The effect of shape of gold nanoparticles in cytotoxicity of prostate cancer cell lines - Soares, S. (2021)
Gold nanoparticles (AuNP) can be applied in medicine to treat many diseases, such as cancer. Over the years, they have attracted a lot of interest for therapies. In this study, we synthetized three different shapes of gold nanoparticles – spherical, stars and rods and analyzed their cytotoxicity in prostate cancer cell lines (PC3, DU145 and LNCaP). Cells were treated with different concentrations of gold nanoparticles, from 0 to 1.0 mM during 24h. The results showed that gold nanoparticles were nontoxic to concentration until 1.0 mM.